DETERMINASI EFEKTIVITAS SISTEM INFORMASI AKUNTANSI: INTEGRASI MODEL TAM DAN TASK–TECHNOLOGY FIT - Nur DP, Emrinaldi; Fitrios, Ruhul (Universitas Riau, 2025)
This study aims to analyze the factors influencing the effectiveness of Accounting Information Systems (AIS) in financial institutions by integrating the Technology Acceptance Model (TAM) and Task–Technology Fit (TTF) frameworks. TAM describes the acceptance of technology by users, while TTF describes the suitability of technology to the needs and complexity of the task. The research is motivated by the rapid digital transformation in Indonesia’s banking sector, particularly in Pekanbaru, which demands information systems that are both effective and adaptive to technological advances. Using a quantitative approach through surveys of bank employees, this study examines the effects of technological sophistication, task complexity, human resource competence, and user participation on AIS effectiveness. The results show that all four factors have a positive and significant influence on AIS effectiveness. Technological sophistication improves efficiency and reporting accuracy, task complexity drives the need for adaptive systems, human competence determines system implementation success, and user participation enhances system acceptance and utilization. Theoretically, this study strengthens the integration of TAM and TTF in explaining AIS effectiveness and provides practical implications for financial institutions to enhance digital readiness and human resource capabilities